Evidence-based guidelines for the pharmacological treatment of schizophrenia: Updated recommendations from the British Association for Psychopharmacology. (January 2020) - Barnes, Thomas RE; Drake, Richard; Paton, Carol; Cooper, Stephen J; Deakin, Bill; Ferrier, I Nicol; Gregory, Catherine J; Haddad, Peter M; Howes, Oliver D; Jones, Ian; Joyce, Eileen M; Lewis, Shôn; et al.
These updated guidelines from the British Association for Psychopharmacology replace the original version published in 2011. They address the scope and targets of pharmacological treatment for schizophrenia. A consensus meeting was held in 2017, involving experts in schizophrenia and its treatment. They were asked to review key areas and consider the strength of the evidence on the risk-benefit balance of pharmacological interventions and the clinical implications, with an emphasis on meta-analyses, systematic reviews and randomised controlled trials where available, plus updates on current clinical practice. The guidelines cover the pharmacological management and treatment of schizophrenia across the various stages of the illness, including first-episode, relapse prevention, and illness that has proved refractory to standard treatment. It is hoped that the practice recommendations presented will support clinical decision making for practitioners, serve as a source of information for patients and carers, and inform quality improvement.